2011
DOI: 10.1095/biolreprod.110.086116
|View full text |Cite
|
Sign up to set email alerts
|

Postejaculatory Increase of Prostatic Triiodothyronine (T3) Depends on Sympathetic Innervation in the Rat1

Abstract: Thyronines are essential for the development of the male reproductive system, including the prostate gland. Metabolically active 3,5,3' triiodothyronine (T(3)) is generated mainly by the extrathyroidal, enzymatic 5'deiodination of the prohormone thyroxine (T(4)), which is catalyzed by deiodinases type 1 (D1) and type 2 (D2). Prostate D1 activity is highly expressed during puberty and declines with age, but continuous, long-term sexual activity prevents this reduction. The aims of this study were to characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Mechanistically, it has been established that PKA activation and/or exchange protein activated by cAMP (EPAC) are crucial thyroid response (60). Tumor D1 activity was not measured, but previous studies have shown a direct correlation between enzyme activity (deiodination) and T3 generation in normal prostate tissue (35). T3 supplements also increased the expression of ARA70a, a prostate epithelium T3-responsive gene; ARA70 is reduced in prostate cancer cells, but its overexpression induces apoptosis and reduces the cell-invasive capacity (61).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanistically, it has been established that PKA activation and/or exchange protein activated by cAMP (EPAC) are crucial thyroid response (60). Tumor D1 activity was not measured, but previous studies have shown a direct correlation between enzyme activity (deiodination) and T3 generation in normal prostate tissue (35). T3 supplements also increased the expression of ARA70a, a prostate epithelium T3-responsive gene; ARA70 is reduced in prostate cancer cells, but its overexpression induces apoptosis and reduces the cell-invasive capacity (61).…”
Section: Discussionmentioning
confidence: 99%
“…In some carcinomas, thyroxine (T4) and triiodothyronine (T3) exert protumoral effects, stimulating cell proliferation and angiogenesis by nuclear (thyroid hormone receptors TRα and TRβ1) and/or nonnuclear mechanisms (αvβ3 integrin receptor/activation of MAPK and phosphoinositide 3-kinase [PI3K] pathways) (19)(20)(21)(22) analytical Methods RIA. Circulating levels of T3 were measured by homologous RIA as previously described (35). The assay contained serum or standards (0.1-4.0 ng T3/mL), hypothyroid serum, anti-T3 antibody (1:2,000) and 125 I-T3 (0.05 ng/mL) in a final volume of 350 μL.…”
Section: Balb/c Nude Mice and Lncap Tumor Inductionmentioning
confidence: 99%
“…The localization of these receptors in the female prostate has not been previously described for any species. However, the presence of deiodinase type 1 and triiodothyronine in the prostate of male rats has been associated with the regulation of proliferation and secretion of epithelial cells (51)(52). Thus, similar functions of thyroid hormones and TSH could be expected for the female prostate.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, DIO1 activity is under endocrine control; it is stimulated by T4, estrogens, and prolactin (PRL) and is negatively regulated by androgens ( 11 ). An association between enzymatic activity and prostatic T3 levels was observed during different physiological challenges ( 12 , 13 ). Nevertheless, the contribution of DIO1 to T3 generation has been questioned in recent years, and instead, it has been suggested that this enzyme contributes to iodine recycling ( 1 , 2 ).…”
Section: Transport Uptake and Bioavailability Of Thyroid Hormones In ...mentioning
confidence: 97%
“…On the other hand, it has been shown that the sympathetic input activated by sexual behavior increases prostate DIO1 activity after consecutive ejaculations ( 13 ). In addition, DIO1 activity is under endocrine control; it is stimulated by T4, estrogens, and prolactin (PRL) and is negatively regulated by androgens ( 11 ).…”
Section: Transport Uptake and Bioavailability Of Thyroid Hormones In ...mentioning
confidence: 99%